The British and Brazilian expeditions and the 1919 total solar eclipse: Regimes of labour and degrees of invisibility - Simões, A.; Soares, H.; Carolino, L. M. (The British Journal for the History of Science, 2025)
In this paper, we dissect how different regimes of labour were crucial to the success of the British and Brazilian expeditions which observed the 1919 total solar eclipse in Príncipe and Sobral. We connect regimes of labour with degrees of invisibility and discuss plausible justifications for various absences/presences in the written records. We discuss reasons for the inclusion of Cottingham, the artisan–technician expert on clockwork mechanisms, into the teams; the entanglements of forced labour with scientific and technical work in Príncipe; and the various regimes of labour in place at Sobral. We argue that the impact of various regimes of labour in Príncipe and Sobral cannot be confined to the provision of infrastructural support, but include critical location choices, the possibility of scientific success during the observations themselves, and the processing of plates following observations.